FLYPAPER EFFECT PADA DANA ALOKASI UMUM ( DAU ) DAN PENDAPATAN ASLI DAERAH ( PAD ) TERHADAP BELANJA DAERAH ( BD ) PADA PEMERINTAH PROVINSI SULAWESI UTARA - Lambut, Adventinus Kristanto; Budiarso, Novi (ACCOUNTABILITY, 2013)
Decentralization leads the broad impact of accounting for local governments. Among other is the separation of powers from the centre, which has been handed to the local  ( including state, province, county, and town) . Even so, the Central Government does not immediately fully release the local goverments. But the Central Government still needs to transfers  intergovernmental grants to the local. One of the funds transfer is General Allocation Fund which can need by the local government freely for either operational expenditure or capital expenditure. The General Allocation Fund  ( Dana Alokasi Uumum )  and the Original Region Revenue  ( Pendapatan Asli Daerah)  are several income account for local governments to be used as Local Expenditure  ( Belanja Daerah) . One example of the waste in the BD can be seen through a phenomenon called the flypaper effect. Where DAU lag 1 is more significantly influential to BD than PAD lag 1. However, in this research gives empirical evidence that in North Sulawesi Province Government for the realization of the budget for the years 2001 until 2010, the flypaper effect phenomenon does not occur. This demonstrared by statistic tool, multiple regression generates the coefficient PAD lag 1 influences significantly to BD with 0.006 on α 0.05 whereas DAU lag 1 does not influence significant.